Peranan Bahasa Indonesia dalam Komunikasi Verbal Antara Desainer dan Konsumen Busana di Era Digital - Dathin Azzura; Rosa Evalinda Gultom; Elprida Yanti Laoli; Putri Gresia Sihombing; Hendra Kurnia Pulungan (Politeknik Kampar, 2025)
This study aims to analyze the role of Indonesian language in verbal communication between designers and fashion consumers in the digital era. Using a qualitative approach through literature studies, this study examines the function of the Indonesian language in building understanding, negotiation, and trust in online fashion transactions. The results of the study show that Indonesian plays three main roles in fashion design communication. First, the cognitive role as a means of expression and representation of design concepts, allows designers to convey ideas clearly and in a structured manner. Second, the pragmatic role as a tool for negotiation and persuasion, serves to avoid product ambiguity and strengthen understanding between the parties involved. Third, the socio-affective role that forms professionalism and emotional closeness, creates a more personal and trusted relationship between designers and consumers. The adaptive use of a variety of formal and non-formal languages has been proven to increase communication effectiveness, consumer satisfaction, and competitiveness of the national fashion industry in the midst of the development of digital technology. These findings underscore the importance of language competence in the context of creative business, particularly in a fashion industry that demands clarity, aesthetics, and strong interpersonal relationships. This research contributes to the development of relevant and contextual communication strategies in Indonesia's digital fashion ecosystem.